Bioactive‐rich Sideritis scardica tea (mountain tea) is as potent as Camellia sinensis tea at inducing cellular antioxidant defences and preventing oxidative stress. (7th June 2013) - Danesi, Francesca; Saha, Shikha; Kroon, Paul A; Glibetić, Marija; Konić‐Ristić, Aleksandra; D'Antuono, Luigi F; Bordoni, Alessandra
Abstract BACKGROUND In several countries, tea (hot‐water infusions of dried Camellia sinensis (CS) leaves) is a major source of antioxidant flavonoids, and its consumption has been associated with several favourable outcomes. Other plants used for the preparation of herbal teas are sources of phenolic antioxidant compounds; among them Sideritis scardica (SS) is used for the preparation of a popular drink throughout Eastern and Central Europe. We have compared the effects of an SS extract to a CS extract in HepG2 cells to set the scientific basis for the exploitation of other herbal teas in counteraction of oxidative stress. RESULTS Although SS extract had a lower phenolic concentration and total antioxidant capacity than CS extract, their cellular antioxidant effects were similar. The different phenolic pattern of the extracts suggests that the protective activity is not limited to catechins. CONCLUSION Although further research is needed, our data represent a first contribution for the evaluation of the potential effect of SS in increasing antioxidant defences. © 2013 Society of Chemical Industry